2021
DOI: 10.1038/s41598-021-91842-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze–thaw cycle on physical and mechanical properties and damage characteristics of sandstone

Abstract: Rock deterioration under freeze–thaw cycles is a concern for in-service tunnel in cold regions. Previous studies focused on the change of rock mechanical properties under unidirectional stress, but the natural rock mass is under three dimensional stresses. This paper investigates influences of the number of freeze–thaw cycle on sandstone under low confining pressure. Twelve sandstone samples were tested subjected to triaxial compression. Additionally, the damage characteristics of sandstone internal microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The existing research has shown that the compressive strength, elastic modulus, Poisson’s ratio, and other mechanical properties of rock gradually decrease with the increase in the water content of rock in the process of freeze–thaw cycle [ 6 , 7 ], Hou et al [ 8 ] found that the water chemical softening mechanism plays an important role in the process of rock freeze–thaw damage. Ren et al [ 9 ] studied the change in mechanical properties and damage mechanism of saturated red sandstone under freeze–thaw and triaxial load.…”
Section: Introductionmentioning
confidence: 99%
“…The existing research has shown that the compressive strength, elastic modulus, Poisson’s ratio, and other mechanical properties of rock gradually decrease with the increase in the water content of rock in the process of freeze–thaw cycle [ 6 , 7 ], Hou et al [ 8 ] found that the water chemical softening mechanism plays an important role in the process of rock freeze–thaw damage. Ren et al [ 9 ] studied the change in mechanical properties and damage mechanism of saturated red sandstone under freeze–thaw and triaxial load.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on this worldwide 16 – 19 . Jin et al adopted a pipe shed advanced support and observed that as the effective range of the one-time support increases, the integrity of the support increases and safety of the construction process increases 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Confinement convergence method and support constraint effect. During underground tunnel construction, the working face has a constraint effect on the surrounding rock after excavation, which gradually weakens as the working face advances and the surrounding rock pressure is slowly released 20,21 . Similar to the constraint effect of the working face, the support structure applied in a tunnel also has a certain constraint effect on the surrounding rock in front of it, which restricts surrounding rock deformation and is herein referred to as the "support constraint effect".…”
mentioning
confidence: 99%